Information and Communication Technology Literacy Skills and Class Instruction: a Comprehensive Perception Survey of University of Benin First Year Students - Luke O. Obasuyi (Nordic Journal of Information Literacy in Higher Education, 2015)
This study investigates the influence of class instruction (GST 111 – use of library) on University of Benin (UNIBEN) first year students’ information and communication technology (ICT) literacy skills. The study adopted the survey research method using the questionnaire as research instrument. First year students in the 2013/2014 academic session constituted the population of study. Simple random and total enumeration sampling methods were used to collect data from students in five out of twelve faculties in the university. The questionnaire used is a 4-point likert scale instrument: SA (Strongly agreed) = 4; A (Agreed) = 3; D (Disagreed) = 2; and SD (Strongly disagreed) = 1. Data was collected at the end of the first semester when the GST 111 – use of library was concluded. Results revealed that Computer, Software, Internet, WWW and ICT literacy skills of the students are high. There is a significant difference in Computer, Software, Internet and WWW and ICT literacy skills of the students per faculty. Majority (65%) of the students are skillful in ICT use. Class instruction is very well perceived by the students and it positively influenced students’ ICT literacy skills. Gender and secondary school attended did not influence students’ ICT literacy skills. There is no significant difference between male and female students’ ICT literacy skills as well as students that attended private or public secondary schools. It is therefore concluded that the students are highly ICT literate and class instruction (GST 111 – use of library) course mainly influenced the students’ ICT literacy skills thus the class instruction programme in the university is adequate and effective.